Reformasi Agraria Joko Widodo-Jusuf Kalla dalam Konsep dan Realita Kepemimpinan yang Fasilitatif (Facilitative Leadership) - Khairul Ikhsan, Adji Suradji Muhammad (Dialektika Publik, 2019)
The The focus of the discussion in this paper will examine leadership theoretically and case studies are seen as an important element in bringing stakeholders to direct them to carry out collaborative processes or what we call Facilitative Leadership. But this concept of leadership is not a traditional leadership concept that has been known. Jokowi-Jusuf Kalla's leadership contains the agenda of the Agrarian Reform which starts from the regions and villages. In the Nine Priority Agenda, also known as Nawacita, it was stated that agrarian reform in the form of direct pledging guarantees legal certainty in land ownership rights, resolving land disputes and opposing the criminalization of the resumption of community land rights. It is interesting to study how the correlation of the National Agrarian Reform Program by the Government of President Joko Widodo is if we relate it to the concept of facilitative leadership.